On the modeling of equilibrium twin interfaces in a single-crystalline magnetic shape-memory alloy sample—III: Magneto-mechanical behaviors - Wang, Jiong; Steinmann, Paul (Continuum Mechanics and Thermodynamics, 2016)
This is the concluding part III of a series of papers. The aim of the current paper is to simulate and analyze the procedure of variant reorientation in a magnetic shape-memory alloy (MSMA) sample and to predict the response of the sample subject to various loading conditions. The sample to be considered in this paper has a 3D cuboid shape and is subject to typical magneto-mechanical loading conditions. Variant reorientation in the sample is realized through twin interface movements. To investigate the key features of twin interface movements, the properties of configurational forces on the twin interfaces are analyzed. For both the stress-assisted MFIS tests and the field-assisted quasi-elasticity tests, the magneto-mechanical behavior of the MSMA sample during the whole loading procedure is simulated by using the finite element method. The influence of the initial variant distribution in the sample on its global response is discussed. The obtained numerical results are compared with the experimental results. It can be seen that the model predictions can fit the experimental results both at a qualitative as well as at a quantitative level.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Configurational force; Finite element method; Magnetic shape-memory alloys; Magneto-mechanical response; Twin interface